2020
DOI: 10.3390/ph13100264
|View full text |Cite
|
Sign up to set email alerts
|

Current Pharmacological Treatment Options for Central Serous Chorioretinopathy: A Review

Abstract: Central serous chorioretinopathy (CSC) is a common cause of visual impairment in patients generally aged 20 to 60 and it is characterized by acute or chronic neurosensory detachments of the retina. Although CSC resolves spontaneously in most cases, in some patients it may cause permanent visual impairment in the working population; for this reason, several approaches, including photodynamic therapy (PDT), subthreshold micropulse laser treatment and oral mineralocorticoid receptor antagonists, have been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 99 publications
(112 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, the role of inflammation has been thought to be involved in the pathogenesis of CSC. 75 The previous study demonstrated that the cause of choroidal vascular hyperpermeability in CSC may be inflammation and free radicals. 11 Besides, the disruption of BRB may cause further inflammation resulting in a protracted disease course and the detachment of the neurosensory retina.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the role of inflammation has been thought to be involved in the pathogenesis of CSC. 75 The previous study demonstrated that the cause of choroidal vascular hyperpermeability in CSC may be inflammation and free radicals. 11 Besides, the disruption of BRB may cause further inflammation resulting in a protracted disease course and the detachment of the neurosensory retina.…”
Section: Discussionmentioning
confidence: 98%
“…Singlet oxygen is short-lived and therefore remains active only in a thin layer of a few millimeters above AMC and cannot accumulate in the environment [ 31 ]. Singlet oxygen has been safely applied in medicine, such as for photodynamic treatment of tumors and age-related macular disease of the retina, for many years [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Singlet oxygen is short-lived and therefore remains active only in a thin layer of a few millimeters above AMC and cannot accumulate in the environment [45]. Singlet oxygen is safely applied in medicine like for photodynamic treatment of tumors and age-related macular disease of the retina for many years [46,47].…”
Section: Discussionmentioning
confidence: 99%